Femtosecond laser processing of optical fibres for novel sensor development - Kalli, Kyriacos; Theodosiou, Antreas; Ioannou, Andreas; Lacraz, Amédéé (My University, 2017)
We present results of recent research where we have utilized a femtosecond laser to micro-structure silica and polymer optical fibres in order to realize versatile optical components such as diffractive optical elements on the fibre end face, the inscription of integrated waveguide circuits in the fibre cladding and novel optical fibre sensors designs based on Bragg gratings in the core. A major hurdle in tailoring or modifying the properties of optical fibres is the development of an inscription method that can prove to be a flexible and reliable process that is generally applicable to all optical fibre types; this requires careful matching of the laser parameters and optics in order to examine the spatial limits of direct laser writing, whether the application is structuring at the surface of the optical fibre or inscription in the core and cladding of the fibre. We demonstrate a variety of optical components such as two-dimensional grating structures, Bessel, Airy and vortex beam generators; moreover, optical bridging waveguides inscribed in the cladding of single-mode fibre as a means to selectively couple light from single-core to multi-core optical fibres, and demonstrate a grating based sensor; finally, we have developed a novel femtosecond laser inscription method for the precise inscription of tailored Bragg grating sensors in silica and polymer optical fibres. We also show that this novel fibre Bragg grating inscription technique can be used to modify and add versatility to an existing, encapsulated optical fibre pressure sensor.
Keywords: Femtosecond laser; Fibre Bragg gratings; Integrated optical circuits; Optical fibre sensors; Polymer fibres